Wide-viewing-angle switchable image splitter obtained using varied-line-spacing H-PDLC Bragg grating. Issue 9 (15th July 2017) - Wang, Kangni; Zheng, Jihong; Liu, Yourong; Lu, Feiyue; Gao, Hui; Zhuang, Songlin
ABSTRACT: We propose the use of a varied-line-spacing (VLS) holographic polymer-dispersed liquid crystal (H-PDLC) Bragg grating as a switchable image splitter to generate a compatible three-dimensional (3D) stereogram and to increase the viewing angle of the observer. To fabricate the VLS grating, a cylindrical lens is adopted to form a cylindrical wave, which interferes with a plane wave, generating an H-PDLC grating with a continuously varying period. The proposed holographic optical element (HOE)-based image splitter comprises two VLS H-PDLC gratings. It can be attached on a designed pattern, with two rectangles taking the place of conventional liquid crystal display panel pixels, and can separate them into right and left viewing fields with a wider range. Experimental results show that the movement of the eyes of the observer can reach 37.6 mm. A theoretical simulation indicates that a shorter focal length of the cylindrical lens can yield a larger movement range. Switching between two-dimensional and 3D modes can be performed by applying an external alternating-current voltage at ~80 V. The contrast ratio of the diffracted images induced by crosstalk is greater than 60%, which indicates the feasibility of the proposed HOE for 3D image splitting. Graphical Abstract: